What does a migraine aura look like?—A systematic review - Joppeková, Ľubica; Pinto, Maria João; da Costa, Mariana Dias; Boček, Richard; Berman, Gabriele; Salim, Yones; Akhtanova, Dinara; Abzalbekova, Aizhana; MaassenVanDenBrink, Antoinette; Lampl, Christian (Journal of headache and pain, 2025)
Migraine with aura is a prevalent neurological disorder that affects up to 30% of individuals experiencing migraines. It presents as temporary neurological disturbances, primarily visual, but also includes sensory, speech, motor, and brainstem symptoms. The underlying pathophysiology is closely tied to cortical spreading depression, which initiates neurovascular and inflammatory changes. Epidemiological studies show significant variations in the prevalence of migraine with aura across different demographics, with a more pronounced effect observed among women. Genetic research has identified both common and rare variants that influence susceptibility to migraine with aura, with genome-wide association studies revealing distinct risk loci. Neuroimaging studies indicate structural and functional alterations in cortical and subcortical areas, reinforcing the role of altered brain connectivity in migraine with aura. Additional studies, including various neurophysiological techniques (such as EEG, VEP, or TMS), are needed to potentially identify specific patterns within MA that would help better characterise clinical and electrophysiological phenotypes. Differential diagnosis is essential, as migraine aura symptoms may overlap with a wide range of primarily neurological paroxysmal disorders. While the treatment of migraine traditionally prioritises the headache, there is limited evidence for targeted therapies addressing aura symptoms; further research is warranted. This systematic review offers a comprehensive synthesis of aura types, epidemiology, genetics, pathophysiology, diagnosis, and management of migraine with aura, emphasising areas for future exploration. Graphical Abstract